Employment and investment in innovation activities without introduction of new technologies: a study on Ecuador - Del Pozo, Diego; Fernández-Sastre, Juan (Estudios de Economía, 2021)
This article estimates the effect of the introduction of technologies and the effect of investing in innovation activities without the introduction of technologies on employment, using data from the Ecuadorian Innovation Survey and the Social Security Institute and applying the inverse probability weighting methodology. The results indicate that only the introduction of new technologies increases total employment in the short run; although investment in R&D, without the introduction of technologies, increases the recruitment of scientists. Finally, firms that introduce technologies increase the hiring of managers, scientists and technicians.